Construction of a Modular Arsenic-Resistance Operon in E. coli and the Production of Arsenic Nanoparticles - Edmundson, Matthew Charles; Horsfall, Louise (Frontiers in Bioengineering and Biotechnology, 2015)
Arsenic is a widespread contaminant of both land and water around the world. Current methods of decontamination such as phytoremediation and chemical adsorbents can be resource and time intensive, and may not be suitable for some areas such as remote communities where cost and transportation are major issues. Bacterial decontamination, with strict controls preventing environmental release, may offer a cost-effective alternative or provide a financial incentive when used in combination with other remediation techniques. In this study we have produced E. coli strains containing arsenic resistance genes from a number of sources, overexpressing them and testing their effects on arsenic resistance. While the lab E. coli strain JM109 (the “wild-type”) is resistant up to 20 mM sodium arsenate the strain containing our plasmid pEC20 is resistant up to 80 mM. When combined with our construct pArsRBCC arsenic-containing nanoparticles were observed at the cell surface; the elements of pEC20 and pArsRBCC were therefore combined in a modular construct, pArs, in order to evaluate the roles and synergistic effects of the components of the original plasmids in arsenic resistance and nanoparticle formation. We also investigated the use of introducing the lac operator in order to more tightly control expression from pArs. We demonstrate that our strains are able to reduce toxic forms of arsenic into stable, insoluble metallic As(0), providing one way to remove arsenate contamination, and which may also be of benefit for other heavy metals.